Evaluación anatómica de 50 especies forestales en el Sur del Ecuador - Armijos Montaño, Andrés Roosevelt (2019)
The study of tropical woods through their anatomical characteristics has taken on greater importance in recent years and is of great importance as a key tool for forest control and management. Therefore, in the present study, an automated classification of forest species according to their anatomical characteristics was carried out using unsupervised statistical methods. Anatomical records of 50 forest species from the Tropical Timber Anatomy Laboratory were used during the 2016-2018 academic period, considering the main 50 anatomical characteristics for each species based on IAWA standards. The statistical analysis to identify similarities between species was carried out by means of dendrograms with clustering type Ward D., correlation matrix (significant r with p < 0.05) and heat maps through the statistical programming platform R. The information and results allowed us to determine that the family and genus do not always influence the anatomical properties of the wood. Vochysia guianensis (Vochysiaceae) and Ficus (aff. cuatrecasana) (Moraceae) even though belonging to different families showed a high similarity between their anatomical characteristics (r = 0.66, p-value: 0.001), the same was the case of Pouteria lucuma and Handroanthus billbergii, Virola Sebifera and Eucalyptus globulus among others. However, in only one case were found significant similarities between species of the same genus as it was with Jacaranda mimosifolia and Jacaranda sparrei (Bignonaceae), and of the same family Cedrela odorata, Swietenia macrophylla, and Guarea kunthiana (Meliaceae). For this reason, it is necessary to continue with more detailed studies related to anatomical characterization, as well as its relationship with the site, and climatic conditions know these differences with greater precision, and to serve us as a tool for the identification and origin of tropical woods. Key words: wood anatomy, correlation, wood identification.